Malaysians’ acceptance towards Korean beauty standards embedded In Korean popular culture / Farah Alia Zaizakrani - Zaizakrani, Farah Alia (Universiti Teknologi MARA, 2021)
The Korean wave or Hallyu which was first coined in the 1990s by a Chinese journalist to describe the wave of Korean pop culture has spread to many Southeast Asian countries such as Malaysia, Indonesia, Thailand, and Taiwan over the years. The Korean wave has been dubbed South Korea’s greatest export as exported cultural products such as Korean dramas, KPOP music and fashion in Asia which have gained a wide acceptance around the world. As media content pervades communities and cultures throughout the world, the globalisation of beauty and appearance ideals is becoming more popular within Asian cultures and continues to increase in influence. South Korean celebrities and idols with perfect visuals and bodies are set as the ideal beauty standard by both local and international audiences. Previous studies have mainly focused on the perceptions of South Korean beauty standards in which research in the Malaysian context has been scarce. Thus, the purpose of this research paper is to understand the acceptance of Malaysians towards the Korean beauty standards embedded in Korean popular culture. The study employs the qualitative method in which content analysis based on library research was conducted to collect data. Malaysians were chosen for this study as they are considered one of the major consumers of Korean popular culture and may be influenced by such mediated content. This concept paper will provide a deep understanding regarding the media-generated behaviour of a population exposed to Korean beauty standards and how they respond to them.